Bardet-Biedl syndrome proteins modulate the release of bioactive extracellular vesicles - Ann-Kathrin Volz (Nature Portfolio, 2021)
Extracellular vesicles (EV) are known to be released from the primary cilium, but the role ciliary proteins play in EV biogenesis remains unexplored. Here, the authors demonstrate increased secretion of small EVs with altered cargo composition from cells with known ciliarelated mutations. Wnt related molecules made up a majority of altered cargo